Lucas and Frobenius pseudoprimes - Rotkiewicz, Andrzej (Annales Mathematicae Silesianae, 2003)
We define several types of Lucas and Frobenius pseudoprimes and prove some theorems on these pseudoprimes. In particular: There exist infinitely many arithmetic progressions formed by three different Frobenius-Fibonacci pseudoprimes.